1999
DOI: 10.1177/095632029901000504
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir Treatment of Skin Lesions Results in Immune Deviation in Mice Infected Cutaneously with Herpes Simplex Virus

Abstract: Clinical observations indicate that the antibody response to herpes simplex virus (HSV) in patients undergoing acyclovir treatment is reduced and, although the exact mechanism is not clear, some authors interpret it as immunosuppression. In order to clarify the mechanism, we cutaneously infected mice with HSV-1 and treated the resulting skin lesions with acyclovir. The immune response to infection and treatment in these mice was then analysed. Acyclovir treatment was given orally (20 mg/kg, three times daily),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One hypothesis, therefore, to explain our data is that a toxic effect of VACV in the infected mice interfered with the immune response to infection during the acute phase and that this allowed a transient survival of infectious virus in the period after withdrawing therapy. Others have reported that ACV may have a subtle effect on the immune response to HSV antigens in mice when administered from early times during the acute phase of virus replication (16). Furthermore, it has been suggested that ACV treatment causes a smaller rise in antibody production than placebo treatment, and this has been interpreted as an immunosuppressive effect of ACV treatment (3,6,12).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis, therefore, to explain our data is that a toxic effect of VACV in the infected mice interfered with the immune response to infection during the acute phase and that this allowed a transient survival of infectious virus in the period after withdrawing therapy. Others have reported that ACV may have a subtle effect on the immune response to HSV antigens in mice when administered from early times during the acute phase of virus replication (16). Furthermore, it has been suggested that ACV treatment causes a smaller rise in antibody production than placebo treatment, and this has been interpreted as an immunosuppressive effect of ACV treatment (3,6,12).…”
Section: Discussionmentioning
confidence: 99%
“…50 Briefly, ELISA plates were coated with HSV-1 (HF) antigen overnight at 4°C. The plates were washed with PBS and blocked with 3% skim milk in PBS.…”
Section: Immunization Determination Of Igg Antibody Production By Elmentioning
confidence: 99%